Evaluation of the Duration of Anti-Tuberculosis Drug Administration on Leukocyte Profiles in Tuberculosis Patients - Ipniliati, Eva; Dwiyanti, Ratih Dewi; Insana, Aima (Baiman Bauntung Batuah Center, 2025)
Tuberculosis (TB) is a global health problem that requires monitoring the immune response during treatment. Leukocyte profile is an important indicator in assessing the body's response to anti-tuberculosis drug therapy. The purpose of the study was to determine the difference in leukocyte profiles in pulmonary TB patients after 0 months and 2 months of anti-tuberculosis drug treatment—analytical research method with cross-sectional design on 60 pulmonary TB patients in Sungai Malang and Karias Health Center. Samples were selected purposively. Leukocyte examination was performed using Hematology Analyzer, and data were analyzed by independent t-test and Mann-Whitney. The results showed a significant decrease in the number of leukocytes (9,877/mm³ to 6,678/mm³, p<0.05), segment neutrophils (68.73% to 51.33%, p<0.05), and a significant increase in lymphocytes (21.07% to 37.33%, p<0.05). Basophils, eosinophils, rod neutrophils, and monocytes showed no significant difference (p>0.05). Conclusion A 2-month anti-tuberculosis drug treatment duration decreased leukocytes and segment neutrophils and significantly increased lymphocytes. Leukocyte monitoring is recommended as an indicator of therapy response.